The Quality Changes and Proteomic Analysis of Cattle Muscle Postmortem during Rigor Mortis - Zhenjiang Ding; Qichao Wei; Chunmei Liu; Hong Zhang; Feng Huang (Foods, 2022)
Rigor mortis occurs in a relatively early postmortem period and is a complex biochemical process in the conversion of muscle to meat. Understanding the quality changes and biomarkers during rigor mortis can provide a theoretical basis for maintaining and improving meat quality. Herein, a tandem mass tag proteomic method is used to investigate the effects of differentially expressed proteins on the meat quality of cattle Longissimus lumborum muscle postmortem (0, 6, and 24 h). The pH, total sulfhydryl content and sarcomere length decrease significantly during storage. In contrast, meat color values (L*, a*, and b*) and the myofibril fragmentation index increase significantly. Altogether, 147 differentially expressed proteins are identified, most being categorized as metabolic enzymes, mitochondrial proteins, necroptosis and ferroptosis proteins and structural proteins. The results also reveal additional proteins that are potentially involved in rigor mortis, such as cardiac phospholamban, acetyl-coenzyme A acyltransferase, and ankyrin repeat domain 2. The current results provide proteomic insights into the changes in meat quality during rigor mortis.